The Principle of Wealth Circulation (Tadawul) and the Concept of Structural Liberation (I'taq) from the Perspective of Maqashid Syariah 'Umran Mazen Hashem - Irfan; Ahmad Djalaluddin; Aunur Rofiq; Muhammad Zainudin (Kartika: Jurnal Studi Keislaman, 2026)
This research aims to deeply analyze the principle of wealth circulation (tadāwul) and the concept of structural liberation (i'taq) as alternative solutions thru the perspective of Maqāşid al-Sharī'ah 'Umran developed by Mazen Hashem. The research method used is qualitative with a type of library research and a descriptive-analytical approach. Data analysis was conducted using content analysis and hermeneutics techniques on Hashem's fundamental works and related Islamic economic literature. The research results show that tadāwul functions as an inclusive circulation mechanism to prevent the stagnation of wealth accumulation among a handful of elites, while also being a vital element for the health of civilization. Meanwhile, i'taq acts as an emancipatory instrument that liberates individuals from systemic dependence on capital owners or state authorities, in order to restore the essence of humanity as a free and responsible khalīfah. The integration of these two concepts within the framework of Maqāşid 'Umran offers a third paradigm that transcends the reductionism of conventional economics by emphasizing the balance between individual moral autonomy and collective welfare. This research concludes that Islamic economics, in Hashem's view, is not merely a policy compromise, but rather an integral civilizational orientation to achieve just and sustainable civilizational development ('umrān). The implications of this research encourage a reorientation of sharia economic policies to focus more on equitable wealth distribution and the elimination of structural oppression